Prevalence of begomoviruses in Trigona fuscipennis and Trigona fulviventris visitors of Jatropha curcas. Issue 2 (15th March 2023) - Carboney-Mejía, Ingrid G.; Ruíz-Toledo, Jovani; Hernández-Reyes, José; Lucio-Castillo, Hermilo; Hernandez-Robledo, Verónica; Torres-Castillo, Jorge Ariel; Torres-de los Santos, Rodolfo
Abstract : It has been reported that stingless bees of the genus Trigona are regular visitors to the Jatropha curcas bioenergetic plant, physic nut. These bees use their mandibular system to extract cellulose and resin from the stem, materials necessary for the construction of nests. The objective of this work was to evaluate the prevalence of begomovirus (BV) in populations of Trigonas visitors of J. curcas in Soconusco, Chiapas, Mexico. Eleven individuals of the genus Trigona were collected in five populations, individuals were grouped as T. fuscipennis and T. fulviventris, using taxonomic clues. Using the PA/PB primers, 79% and 69% of T. fuscipennis and T. fulviventris, respectively, had BVs. The results suggest that bees of the genus Trigona could be transmitters of BV, a potential risk in the crop J. curcas .